Extraction of oil from flaxseed using three phase partitioning techniques - Rizvi, Qurat ul Eain Hyder; Sharma, Vasudha; Shams, Rafeeya; Dar, Aamir Hussain; Jan, Bisma; Manzoor, Arshied (Journal of Postharvest Technology, 2021)
Flaxseed used for the extraction of oil has various health benefits as the risks of various chronic diseases are reduced. Flaxseed oil has gained a great importance because of its edible oil which is considered to contain fantastic source of omega-3 fatty acid Alpha Linolenic Acid, proteins, lignans, minerals, vitamins etc. Because of its omega-3 fatty acid content it is used to reduce the risk of various heart diseases. Three-phase partitioning is an efficient bio separation method used for oil extraction from flaxseeds. In this process three phases are formed. These phases are organic phase, intermediate and aqueous phase. In the top layer solvent is present in intermediate layer protein and slurry is present and in lower aqueous phase water is present. In tpp, centrifugation for 15 min at 3000 rpm was done to obtain three phases then upper phase is transferred to the flask for Rota evaporation to remove the solvent and get the oil percentage. Different parameters were optimized to get the higher percentage of oil such as ammonium sulphate, t-butanol, and petroleum ether, solvent to slurry ratio and protease enzyme. The maximum percentage of oil was obtained at 40 % ammonium sulphate, t-butanol & petroleum ether ratio to slurry ratio (1:1).